Role of Parent-Adolescent Communication to Prevent Cyberbullying in Youth: Challenges and Oppertunities - Ghulam Abbas (International Journal for Electronic Crime Investigation, 2024)
The rise of digital technology and social networks has caused an increased rate of cyberbullying cases, predominantly among adolescents. Problematic use of the internet and cyberbullying have had important psychological, social, and emotional impacts on youth, making it a tenacious concern for educators, parents, and policymakers. Effective parent-adolescent/youth communication arises as an essential approach to alleviating the risks and effects of cyberbullying. This review study aims to explore the role of open and helpful communication between youth and parents to avoid cyberbullying. Investigating the various communication approaches and their effect on youthful behavior, the review augments the importance of adopting a helpful and thoughtful environment at homes and educational institutes. The review suggests that youths who are involved in regular frank discussions with parents and teachers about online activities are less prone to cyberbullying. Moreover, the study stresses the need for parents and teachers to be well-familiar with digital/social platforms and cyberbullying dynamics to successfully guide the youth. Educating the parents, teachers, and youth aimed at enlightening communication skills amongst youths, parents and teachers demonstrates promise in decreasing the cyberbullying cases in Pakistan. Therefore, this manuscript intends to explore approaches that involve universities, digital platforms, and communities to support parent-adolescent communication to create safe online environments for the youth.